A Third Wave of Selective Exposure Research? The Challenges Posed by Hyperpartisan News on Social Media - Barnidge, Matthew (2019)
Hyperpartisan news on social media presents new challenges for selective exposure theory. These challenges are substantial enough to usher in a new era—a third wave—of selective exposure research. In this essay, we trace the history of the first two waves of research in order to better understand the current situation. We then assess the implications of recent developments for selective exposure research.